2012
DOI: 10.1097/mat.0b013e31824c38c8
|View full text |Cite
|
Sign up to set email alerts
|

Tinzaparin Is Safe and Effective in the Management of Hemodialysis Catheter Thrombosis

Abstract: Children on hemodialysis are at increased risk of thrombosis, especially when dialyzed via a central venous catheter (CVC); there are limited published data regarding the safety and efficacy of tinzaparin in this group. We conducted a retrospective chart review of all children in the National Pediatric Hemodialysis Centre for Ireland diagnosed with a CVC thrombus and treated with subcutaneous tinzaparin over a 10 year period. Seven children were treated with subcutaneous tinzaparin for 10 CVC thrombi. Tinzapar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Ten individuals, aged between 7 months and 15 years, were identified, and the starting dose was not adjusted for age. There were no episodes of bleeding, but there was a higher rate of recurrence (10%), which may be explained by the need to maintain central venous access . Other studies have confirmed the efficacy and safety of other LMWHs, such as enoxaparin and dalteparin .…”
Section: Discussionmentioning
confidence: 81%
“…Ten individuals, aged between 7 months and 15 years, were identified, and the starting dose was not adjusted for age. There were no episodes of bleeding, but there was a higher rate of recurrence (10%), which may be explained by the need to maintain central venous access . Other studies have confirmed the efficacy and safety of other LMWHs, such as enoxaparin and dalteparin .…”
Section: Discussionmentioning
confidence: 81%
“…Given that unmodified heparin is known to interact with several hundred proteins (Ori et al, 2008), many of them involved in cell signalling and regulation, it is perhaps surprising that heparin administration does not elicit more side-effects in patients undergoing anticoagulant therapy (Cestac et al, 2003;Quinlan et al, 2012). While this is encouraging for those aiming to develop alternative treatments employing a heparin scaffold, it does present something of a puzzle, and the explanation may lie in the interconnected nature of these signalling and regulatory systems.…”
Section: Discussionmentioning
confidence: 99%